Biodegradation of sulfamethazine by Trametes versicolor: Removal from sewage sludge and identification of intermediate products by UPLC–QqTOF-MS - García Galán, María Jesús (2011)
Degradation of the sulfonamide sulfamethazine (SMZ) by the white-rot fungus Trametes versicolor was assessed. Elimination was achieved to nearly undetectable levels after 20 h in liquid medium when SMZ was added at 9 mg L−1 . Experiments with purified laccase and laccase-mediators resulted in almost complete removal. On the other hand, inhibition of SMZ degradation was observed when piperonilbutoxide, a cytochrome P450-inhibitor, was added to the fungal cultures. UPLC–QqTOF-MS analysis allowed the identification and confirmation of 4 different SMZ degradation intermediates produced by fungal cultures or purified laccase: desulfo-SMZ, N4 -formyl-SMZ, N4 -hydroxy-SMZ and desamino-SMZ; nonetheless SMZ mineralization was not demonstrated with the isotopically labeled sulfamethazine-phenyl-13C6 after 7 days. Inoculation of T. versicolor to sterilized sewage sludge in solid-phase systems showed complete elimination of SMZ and also of other sulfon amides (sulfapyridine, sulfathiazole) at real environmental concentrations, making this fungus an interesting candidate for further remediation research.